System Design for Japanese Language Education for Foreign Residents in Japan: Issue of Following the Enforcement of the Promotion of Japanese Language Education Act - Kamiyoshi, Uichi (Intercultural Education, 2020)
Recently, both the number of visitors arriving in Japan and the number of foreign residents living in Japan have reached a record high every year. The revised Immigration Control and Refugee Recognition Act was passed and enacted in the Diet in December 2018, and the acceptance of foreign workers started in earnest in April 2019 with the implementation of the “specified skilled worker” residency status. This represents a major change in the Japanese government’s immigration policy. Since the 1990s, the government has been promising to “actively accept highly skilled foreign workers, while carefully considering foreign workers.” In June 2019, the Promotion of Japanese Language Education Act was promulgated and enforced.In this paper, I will first outline Japan’s recent policy on accepting foreigners. Next, I will provide an historical summary of the discussion surrounding Japanese language education legislation. Then, based on the basic idea that governs the Promotion of Japanese Language Education Act, I will discuss pertinent issues from the following three viewpoints: the Japanese language education popularization plan, quality improvement in Japanese language education, and the continuation of Japanese language learning. Finally, I will discuss the role of Japanese language education in Japan as an “immigrant society.”